Reimagining faith and management : the impact of faith in the workplace - Pio, Edwina, 1955-; Kilpatrick, Robert; Pratt, Timothy (Management, organizations and society (London, England), 2021)
"Much contemporary research ignores or is dismissive of the growth of global religiosity, even though 90% of the global population sees the world through a commitment to some kind of faith. Reimagining Faith and Management addresses this issue and extends the research on the impact of faith in the various aspects of management, such as negotiation, leadership, entrepreneurship, governance, innovation, ethics, finance and careers. Faith impacts how individuals and organisations envision, manage and respond to their various stakeholders, communities, the natural environment and the world around them. This book presents various facets of how faith, values and/or ideological outlook which informs, influences and adds mystery that inspires and impels individuals and organisations. The twenty-one chapters are based on academic research and offer practical managerial recommendations. The book is divided into three sections: Faithful futures impacting individuals; Faithful futures impacting organisations; and Faithful futures impacting society. Each chapter presents a theoretical base and includes practical implications. The book is therefore ideal reading for educators, researchers and students of business, management, career studies, faith-based organisations, corporate governance, and business ethics, as well as religious studies, including applied theology"--